Psychosemantic analysis of eye care workers' percepts of creative abilities - N. V. Rodina; B. V. Biron; V. O. Suslova; A. V. Kernos; O. S. Grytsenko (Ukrainian Society of Ophthalmologists, 2021)
Background: This article puts the emphasis on the notion of "creative abilities" in the context of its interpretation by eye care workers. Creative potential is essential for the general and professional culture of physicians, and personal creativity takes on a new meaning in the age of digitalization and dominance of artificial intelligence in routine medical practice. Purpose: To investigate eye care workers' percepts of creative abilities by conducting a psychosemantic analysis and considering these percepts as a source of health care workers' job satisfaction. Material and Methods: The study sample was composed of the eye care workers from the Filatov Institute of Eye Diseases. Two hundred and eleven eye care workers were requested to take part in the study, and the response rate was 85.8% (181/211). The 181 responders included 99 nursing staff members and 82 physicians (ophthalmologists). The study was conducted with the use of Hughes and Powell's Guiding Principles for Life (GPL) Questionnaire (adapted by Semeniuk), the Kim, Leong, and Lee's Job Satisfaction Scale (JSS) (adapted by Semeniuk) and the Lüscher 8-color test. Results: Eye care workers rated "Creativity" low among the 22 "Guiding Principles for Life". In physicians, such guiding principles as "Creativity", "Devout", and "Material wealth" were associated with each other, which indicates that the achievement of material wealth was associated with such a virtue as devout, and this achievement requires creativity. It was demonstrated that creativity as a guiding principle was more important for physicians than for the nursing staff, and in male physicians it was associated with unconscious satisfaction with working environment.